2012
DOI: 10.1177/0093650212439205
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Effects of Game Framing and Journalistic Adjudication on Cynicism and Epistemic Political Efficacy

Abstract: An online experiment tested the influence of "he said/she said" coverage versus active adjudication of factual disputes, as well as strategy versus policy framing in postdebate news coverage. Adjudication in policy-framed stories increased epistemic political efficacy (EPE), a measure of confidence in one's own ability to determine the truth in politics. However, adjudicated policy stories also elicited greater cynicism than passive policy framing. This suggests a caveat for the spiral of cynicism, calling int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The study also controls for the effect of people's political efficacy on participatory behaviors as this construct has also been observed as a proxy to political participation (i.e., Pingree, Hill, & McLeod, ). Researchers suggest that some items used to measure internal efficacy, such as “people like me don't have any say about what the government does,” may be problematic because they could be measuring both internal and external efficacy at the same time (see Morrell, ).…”
Section: Methodsmentioning
confidence: 99%
“…The study also controls for the effect of people's political efficacy on participatory behaviors as this construct has also been observed as a proxy to political participation (i.e., Pingree, Hill, & McLeod, ). Researchers suggest that some items used to measure internal efficacy, such as “people like me don't have any say about what the government does,” may be problematic because they could be measuring both internal and external efficacy at the same time (see Morrell, ).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, both experimental and observational studies have demonstrated that negative media content increases cynicism. Specifically, much of the recent literature asserts that cynicism is most common when at UNIV OF VIRGINIA on June 21, 2016 jmq.sagepub.com Downloaded from information is not framed around issues (de Vreese & Elenbaas, 2008;Pingree, Hill, & McLeod, 2013). In essence, these game-framed/publicity-framed news stories feed into negative reactions to politics more generally, which result in political disengagement.…”
Section: The Role Of Cynicism and Skepticism In Information Seekingmentioning
confidence: 99%
“…This construct has been shown to have a strong relationship to political participation (Pingree, Hill and McLeod, 2012). Due to validity problems found with some of the traditional scales used to measure internal efficacy (Morrell, 2003), this study follows the operationalization of the concept suggested by Bennet (1997), using only one item: "I think people like me can influence government."…”
Section: Control Variablesmentioning
confidence: 99%